The Routledge companion to architectural drawings and models : from translating to archiving, collecting and displaying - Goffi, Federica (Abingdon, Oxon ; New York : Routledge, 2022)
"Architectural drawings and models are instruments of imagination, communication, and historical continuity. The role of drawings and models, their ownership, placement, and authorship in a ubiquitous digital age deserves careful consideration. Expanding on the well-established discussion of the translation from drawings to buildings, this book fills a lacuna in current scholarly publications, questioning the significance of the lives of drawings and models after construction. Including emerging, well-known and world-renowned scholars in the fields of architectural history and theory and curatorial practices, the 35 contributions define recent research in four key areas: Drawing Sites/Sites of Knowledge Construction: Drawing, Office, Construction Site; The Afterlife of Drawings and Models: Archiving, Collecting, Displaying and Exhibiting; Tools of Making: Architectural Representations and their Apparatus Over Time; The Ethical Responsibilities of Collecting and Archiving: Authorship, Ownership, Copyrights, and Rights to Copy. The research covers a wide range of geographies and delves into the practices of such architects as Sir John Soane, Superstudio, Viollet-le-Duc, Frank Lloyd Wright, Wajiro Kon, Germán Samper Gnecco, A+PS, Mies van der Rohe and Renzo Piano"--
Drawing sites/Sites of knowledge construction -- The afterlife of drawings and models -- Tools of making and knowledge construction -- The ethical responsibilities of collecting and archiving.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Architectural drawing; Architectural models